STUDY OF 3D SEISMIC VELOCITY STRUCTURE TOMOGRAPHY BENEATH GUNTUR VOLCANO FOR JANUARY 2015 UNTIL DECEMBER 2016. - ESTI IRMAWATI - NIM: 12313007, DIAN
Guntur volcano is a volcano complex located in Garut, West Java. Since the last eruption in 1847 until now Guntur volcano was in a period of no eruption. This Guntur volcano activity is further characterized by the recorded volcanic earthquakes. There needs to be mitigation of Guntur volcano considering the demographics of the dense population around it. The form of mitigation that can be done is monitoring about earthquakes and subsurface condition. In this study, the authors determine the location of hypocenter and tomography inversion using data recorded on 6 stations in January 2015 to December 2016 to imaged the 3D seismic velocity structure beneath the Guntur volcano complex. The stages are picking 117 events using LS7 software with 480 P wave and 349 S wave phases, determining the initial location of hyposenter using Geiger method, update 1D velocity model and hypocenter location using VELEST software, tomography inversion and hypocenter relocation using SIMULPS software and resolution test using restoring resolution test, derivative weight sum, and diagonal resolution elements. The results show that events around Guntur volcano have hypocenters between 0 km to 12,88 km below sea level with epicenter tend to concentrate along Gandapura to Guntur. From the interpretation that have been done on the horizontal section of the tomogram Vp, Vs and Vp/Vs at depth of -1 km, 0 km and 1 km below sea level and vertical cross section C-C' of tomogram Vp with resolution limit diagonal resolution element 0.1, derivative weight sum 200 and restoring resolution test there were 3 velocity anomaly zone. Low Vp anomaly patterns at depth of 1 km to the surface that can be interpreted as alterated rock zones, high Vp anomaly at depth of 1 km to 3 km can be interpreted as solid rock and low Vp anomaly at depth of 3 km to 7 km below sea level may be interpreted as a hot volcanic material zone.